# 7.

3 Proving Trigonometric Identities
When listening to Mr. Burger on how to prove trig identities he stated that you might want to work with both sides and come to common end statement. I think of proving trig identities the same way you did proofs in geometry. You typically want to work with one side, massage it, and hopefully you will create the expression on the other side of the equal sign. These types of problems should be viewed as ‘given a problem and its answer, how do you get to the answer?’. You want to keep in mind all of the trig identities you have been exposed to thus far to assist you in proving trig identities. Example Prove:
1 + tan θ = tan θ 1 + cot θ

By examining both sides of the equal sides, it appears that you want to begin with the left side in order to create the right side. sin θ 1+ 1 + tan θ cos θ = 1 + cot θ 1 + cos θ sin θ cos θ sin θ + = cosθ cosθ sin θ cos θ + sin θ sin θ cos θ + sin θ cos θ = sin θ + cos θ sin θ =
cosθ + sin θ sin θ + cosθ ÷ cos θ sin θ cos θ + sin θ sin θ · cos θ sin θ + cos θ sin θ = tan θ cos θ

=

=

The reason why it was best to convert in terms of sine and cosine is because the resultant tan θ is a trig function that can be expressed that way. There will be times when you will have to begin with the right side of the equal sign and work your way to create the left side of the equal sign.

Try the following: Prove. 1 − cos x = sin x tan x 1. cos x 2. cot α + tan α = sec α csc α sec 2 θ − tan 2 θ =1 2 2 2 2sin θ + 2 cos θ

3.

Answers: 1 1 cos 2 x − cos x = − cos x cos x cos x 1 − cos 2 x = cos x sin 2 x sin x sin x sin x = = = sin x = tan x sin x = sin x tan x cos x cos x cos x
cot α + tan α = cos α sin α + sin α cos α cos 2 α sin 2 α = + sin α cos α sin α cos α cos 2 α + sin 2 α 1 1 1 = = ⋅ = csc α sec α = secα cscα = sin α cos α sin α cos α sin α cos α

sec 2 θ − tan 2 θ 1 = 2 2 2 2sin θ + 2 cos θ 2 ( sin θ + cos 2 θ ) = 1 1 = 2(1) 2